National Survey of Pharmacy Leadership at Ministry of Health in Saudi Arabia: Performances Management - Alomi, Yousef Ahmed; Abdulmohsen Albaz, Modhi; AlMuhraj, Wejdan Fawzan; AlKharji, Mashael Yasser; Alshuraym, Norah Rushud (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of pharmacy leadership at the Ministry of Health with emphasis on pharmacy Performance management. Methods: It is a ninety days cross-sectional national survey of pharmacy leadership practice at Ministry of Health. The survey modified from self-assessment of 360 leadership and with pharmacy leadership literature. It consisted of a demographic section, leadership pathway, and fifty-three leadership questions. It contained selected eighteen leadership skills of 360 leadership self-assessment. The electronic format of the survey through the survey monkey system and distributed through emails. All analysis is done through the survey monkey system. The survey divided into several parts for analysis, and discussion. Part one: practice management, part two: planning and organizations, part three: communications strategies, part four: problem-solving and decision making, part five: performances management, part six; working environment, and part seven: professional development. The study explored the part number five; performance management. Results: The survey distributed to one hundred hospitals, the response rate, was forty-two hospitals (42%) with seventy-pharmacy leaders. The gender distribution of responders was Male 43 (63.24%) and female 25 (36.76%) while the nationality was Saudi 69 (98.57%) and non-Saudi 1 (1.43%). The majority of responders were in the age range (25-34) years 30 (55.12%) and (35-44 years) 26 (38.24%). The average score Analytical skills were 2.43 (81.2%) with the highest score was Asks the “right” questions to evaluate situations 2.51 (83.65%). While average score Excellence skills were 2.44 (81.25 %) with the highest score was Produces high-quality work 2.6 (86.65%). The average score Administrative skills were 2.53 (84.32%) with the highest score was Completes reports on-time 2.67 (88.99%). The Attitude skills average score was 2.61 (86.99%) with the highest score was treated all people relatively and with respect 2.68 (89.32%). The attitude skills average score was 2.64 (87.99%) with the highest score was the leaders are not afraid to take corrective action when necessary 2.67 (88.99%). Conclusion: The performance management skills, including analytical, excellence, attitudes, actions and administration skills for pharmacy leaders is critical. The pharmacy leaders had good starting and not acceptable finishing performances through those skills. The pharmacy leaders need practical training of leadership skills through the residency pharmacy practice pro at the Ministry of Health institutions in the Kingdom of Saudi Arabia.
Keywords: Pharmacy leadership; Performances management; Ministry of health; Saudi arabia